WEB-BASED BPS PARTNER MONITORING INFORMATION SYSTEM FOR SOUTH COAST BASED - Ramadhan, Irvon Junet; Weriza, Jusmita (JENTIK, 2024)
In the digital era, effective and efficient data management is very important, especially in government organizations such as the Central Statistics Agency (BPS). This project aims to design and implement a web-based BPS Pesisir Selatan Partner Monitoring Information System, which aims to facilitate monitoring and management of BPS partner data in Pesisir Selatan Regency. This system is built using the Waterfall method, which allows gradual software development starting from the analysis, design, implementation, to testing stages. For system design, the Unified Modeling Language (UML) is used to visually model system requirements and workflows. The PHP programming language was chosen for the development of this system because of its flexibility in developing web applications and its support for various databases. The result of this system development is a web application that can be used by BPS to monitor partner performance and activities in real-time, accelerate the decision-making process, and improve work efficiency. With this system, it is hoped that the management of BPS Pesisir Selatan partners can be carried out in a more structured and accurate manner.